Public Administration and Economic Analysis of the Region along Slovakia’s Southern Border: Partial Comparison with Neighbouring Counties in Hungary - Horbulák, Zsolt; Hegedűs, Szilárd; Lentner, Csaba (Public Governance, Administration and Finances Law Review, 2023)
The paper analyses the economic situation of the districts located along the Southern border of Slovakia, which have sizeable Hungarian-speaking populations. Unemployment ratios, industrial pay levels and corporate profitability figures make up the backbone of the analysis. Our research reveals that, as a whole, the Southern districts fall short of the national average in terms of all economic and demographic indicators. In our research focusing on Slovakia, we have demonstrated the disadvantaged economic situation of the Southern part of the country, where its Hungarian population is concentrated, noting that this may further weaken its ability to retain their population. We used the same methodology for our analysis of the Northern Hungarian counties bordering on Slovakia. In both countries, there are discrepancies between Western and Eastern regions.